Effect of metal wire and glass fibers on the impact strength of acrylic denture-base resin - jaber, Makarem (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): The aim of this study is to compare the impact strength of a heat cured denture-base acrylic resin reinforced with metal wire and glass fibers. Methodology: Forty five specimens were prepared from pink heat cure acrylic resin. Specimens were grouped into; group-I (control group) which consists of 15 specimens with no reinforcement, group-II which consists of 15 specimens reinforced with metal wire, and group-III consists of 15 specimens reinforced with glass fibers. Specimens were tested by using charpy impact machine. Results: The result showed that there was a highly significant difference in impact strength value among the testing groups at (P < 0.001). Conclusion: The impact strength of heat polymerized denture-base resin was enhanced considerably by using metal wire and glass fibers reinforcements. However, the addition of glass fibers was significantly more effective method to improve impact strength of denture base acrylic resin.